Impact of goodwill on firms capital structure in developed and developing countries: moderating effects of legal system - Thakur, Oli Ahad; Amin Noordin, Bany-Ariffin; Matemilola, Bolaji Tunde; Alam, Md. Kausar (Taylor and Francis Group, 2023)
The study investigates the impact of goodwill assets on firms’ capital structure and examines the indirect impact of the legal system on the relationship between goodwill assets and firms’ capital structure (debt ratio). The study uses 4912 firms from 23 developing countries covering the 2010 to 2018 periods. The findings show a robust positive relationship between goodwill assets and firms’ capital structure in developing countries. Moreover, the country’s legal system positively impacts the firms’ capital structure. Furthermore, the impact of goodwill assets on firms’ capital structure is weaker in countries where common law is practiced.